Enhanced Anticancer Activity of Hymenocardia acida Stem Bark Extract Loaded into PLGA Nanoparticles - Oluwasegun Adedokun; Epole N. Ntungwe; Cláudia Viegas; Bunyamin Adesina Ayinde; Luciano Barboni; Filippo Maggi; Lucilia Saraiva; Patrícia Rijo; Pedro Fonte (MDPI AG, 2022)
Hymenocardia acida (H. acida) is an African well-known shrub recognized for numerous medicinal properties, including its cancer management potential. The advent of nanotechnology in delivering bioactive medicinal plant extract with poor solubility has improved the drug delivery system, for a better therapeutic value of several drugs from natural origins. This study aimed to evaluate the anticancer properties of H. acida using human lung (H460), breast (MCF-7), and colon (HCT 116) cancer cell lines as well as the production, characterization, and cytotoxicity study of H. acida loaded into PLGA nanoparticles. Benchtop models of Saccharomyces cerevisiae and Raniceps ranninus were used for preliminary toxicity evaluation. Notable cytotoxic activity in benchtop models and human cancer cell lines was observed for H. acida crude extract. The PLGA nanoparticles loading H. acida had a size of about 200 nm and an association efficiency of above 60%, making them suitable to be delivered by different routes. The outcomes from this research showed that H. acida has anticancer activity as claimed from an ethnomedical point of view; however, a loss in activity was noted upon encapsulation, due to the sustained release of the drug.